'My body is Korean, but not my child's ...': a Foucauldian approach to Korean migrant women's health-seeking behaviours in the UK - Lee, Jeung Yeon (2010)
This thesis examines the health-seeking behaviours of Korean migrant women living in the UK. Theoretically, it argues for treating migration as a process of 'subjectivisation', in the specific sense in which this concept is employed in the work of Michel Foucault, and cliams that migrants' health-seeking behaviours always presuppose and refer back to a fundamental process of assuming, appropriating and manifesting the dominant form(s) of subjectivity within the domain of medicine of the host country-in the case of the UK, the medical subjective form of the 'active patient' and/or 'healthy citizen'. In the present work I show that Korean migrant women tend to resist this process of becoming subject to the ideal active patient model until they happen to undergo some profound and life-altering experience that forces them to come to terms with the British system and its ideal forms of knowledge and behaviour. For (but not all) Korean migrant women, this life-altering experience is that of pregnancy, delivery and childbearing. Pregnancy and childbirth constitute the turning point in a process of subjectivisation and culminates in the institution of a dual medical citizenship. In other words, while they never totally reject their former autochthonous mode of medical subjectivity ('good patient'), they nevertheless come more and more to appoximate the British model subjective form. On the other hand, when it comes to their children, who are ethnically Korean but born and raised in the UK, they tend almost fully to surrender to the British ideal, recognising that their childrn, while Korean, nevertheless possess originally British bodies that demand British treatment. This causes them to become extra vigilant and resourceful regarding their health-seeking behaviours, bringing them more fully in line with the ideal form of medical subjectivity of the active/healthy citizen.